PENGARUH FITUR SISTEM INFORMASI SMARTPHONE DAN INSTAGRAM TERHADAP PERILAKU PENGGUNA: STUDI KASUS PERILAKU ALTRUISTIK DI KOTA BATAM - Anbarwati, Aini Iswanela; Eryc, Eryc (Universitas Dharmawangsa, 2025)
The advancement of smartphone technology and social media platforms, particularly Instagram, has transformed human interaction and encouraged altruistic behaviors such as digital donations and participation in social campaigns. This study examines the influence of smartphone features and Instagram functionalities on altruistic behavior among users in Batam City, Indonesia, a region known for its high technological adoption and diverse demographics. A quantitative approach was employed, collecting data from 400 respondents through purposive sampling. The findings reveal that Instagram features, such as Stories, hashtags, and direct messages, along with smartphone functionalities like notifications and recommendation algorithms, significantly enhance empathy and social engagement. This study provides insights for developers to optimize social engagement features and for policymakers to design community-driven programs. Future research should explore the adaptability of these features across different demographic and geographic contexts.